Analisis Afiksasi dalam Bahasa Lintang Kecamatan Pendopo Kabupaten Empat Lawang - Adisel, Adisel; Welti Wediasti (LITERATUR: Jurnal Bahasa, Sastra dan Pengajaran, 2025)
This study aims to describe the forms, functions, and meanings of affixation in the Lintang language spoken by the community in Pendopo District, Empat Lawang Regency. The research focuses on types of affixes, namely prefixes, suffixes, and confixes, as well as their roles in word formation and semantic change. The method used is descriptive qualitative with data collected through interviews, direct observation, and recordings of daily conversations from six native speakers. The data were analyzed through the stages of reduction, presentation, and conclusion drawing. The results show that affixation in the Lintang language consists of three main types: prefixes, suffixes, and confixes. Prefixes are the most dominant, particularly maN-, ba-, and paN-, which function to form active verbs, indicate professions, tools, or places. The suffix -an is used to form nouns denoting results of activities, while the confix ke- -an is used to form abstract nouns. Affixation in the Lintang language not only serves as a word-formation process but also reflects cultural aspects, social structures, and the worldview of its speakers. In conclusion, affixation plays a crucial role in enriching both morphological structures and semantic meanings in the Lintang language. It functions not only as a grammatical mechanism but also contributes to the preservation of local languages and the understanding of regional linguistics.   Keywords: Affixation, Dialect, Lintang language, Morphology